Thermogravimetric investigation of a new intranasal gel with noopept - B. S. Burlaka (Фармацевтичний журнал, 2019)
Recently, in the world, there is a negative dynamics of increasing diseases of the central nervous system. Creation of neuropeptide-based dosage forms with high pharmacological activity, neuroavailability and improved biopharmaceutical properties is an urgent problem today. The development of a novel intranasal dosage form with noopept that has high neuroavailability and therapeutic efficacy deserves attention. The purpose of the work is to conduct thermogravimetric studies to substantiate the possibility of combining active and auxiliary substances in a new intranasal gel with noopept and to characterize its temperature mode of manufacture.